The Role and Duties of Supervising Judges and Inmate Observers at Class I Medan Tanjung Gusta Penitentiary - Immanuel Pasaribu; Marlina Marlina; Wessy Trisna (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyse the legal provisions governing the roles and duties of supervisory judges and observers in relation to prisoners, examine their implementation at the Medan Tanjung Gusta Class I Prison, and identify obstacles that arise in the supervision and observation process. The study focuses on the effectiveness of the implementation of judges' authority in ensuring that prisoners' rights and the objectives of correctional institutions are fulfilled. The research method used was descriptive normative-empirical legal research with a legislative and case approach. The research data consisted of primary and secondary data collected through literature and field studies, which were then analysed qualitatively with deductive conclusions. The results of the study show that the regulation of the roles and duties of supervisory and observer judges is stipulated in Articles 277 to 283 of the Criminal Procedure Code, Article 55 of Law Number 48 of 2009 concerning Judicial Authority, and Supreme Court Circular Letter Number 7 of 1985. However, its implementation at the Medan Tanjung Gusta Class I Prison has not been optimal. This is due to differences between the judges' statements and the statements of prison officials and prisoners, as well as various obstacles covering aspects of legal substance, legal structure, and legal culture. This study concludes that regulatory reforms are needed to clarify the roles of supervisory judges and observers, increase the transparency and accountability of supervision, and strengthen judicial resources so that the supervision of prisoners can be carried out more effectively and fairly.